Update on hypoxia-inducible factors and hydroxylases in oxygen regulatory pathways: from physiology to therapeutics - Ratcliffe, P; Koivunen, P; Myllyharju, J; Ragoussis, J; Bovée, J; Batinic-Haberle, I; Vinatier, C; Trichet, V; Robriquet, F; Oliver, L; Gardie, B (Dove Medical Press, 2017)
The “Hypoxia Nantes 2016” organized its second conference dedicated to the field of hypoxia research. This conference focused on “the role of hypoxia under physiological conditions as well as in cancer” and took place in Nantes, France, in October 6–7, 2016. The main objective of this conference was to bring together a large group of scientists from different spheres of hypoxia. Recent advances were presented and discussed around different topics: genomics, physiology, musculoskeletal, stem cells, microenvironment and cancer, and oxidative stress. This review summarizes the major highlights of the meeting.